ICT INTEGRATION IN FOREIGN LANGUAGE TEACHING IN VIETNAMESE HIGHER EDUCATION: LANGUAGE TEACHERS’ PERSPECTIVES - Nguyen, Dung Tien (Universitas Islam Sumatera Utara (UISU), 2025)
Information and communication technology (ICT) has been conducting sweeping changes in higher education worldwide. With its focus on communication and interaction, language education can be immensely benefitted from various available ICT tools. A number of studies have been conducted in the field of ICT application in language education, but the perspective of language teachers in Vietnamese higher education – a pivotal part – is not thoroughly studied. Hence, this research investigated the issue of ICT integration in foreign language teaching in Vietnamese higher education from the perspective of language teachers. Using the descriptive qualitative method, the research employed the instrument of interview with 87 teachers of different foreign languages from a number of tertiary institutions in Vietnam. The findings showed that various ICT tools were used in their foreign language teaching for different purposes and can be grouped into 06 groups according to their functions in use. Such ICT integration resulted in more effective teaching, learning, assessment, class management, and students’ higher learning motivation and better language learning outcomes. The ICT tools were acknowledged to help with the development of the four macro-language skills as well as vocabulary. To promote ICT integration in language teaching, supportive school leadership and policy frameworks alongside with ICT training for language teachers are required. In short, this research has provided insights into how ICT can be more effectively integrated into language teaching practices in Vietnam.